Thermal decomposition reaction of cis-6-phenyl-5,6-(2-phenyl-propilydene)- 3,3-tetramethylene-1,2,4-trioxacyclohexane in different solvents - Cafferata, Lázaro F. R. (2000)
The kinetics of the thermal decomposition reaction of cis-6-phenyl-5,6-(2- phenyl-propilydene)-3,3-tetramethylene-1,2,4-trioxacyclohexane (I) was investigated in the temperature range of 100-130°C in selected solvents of different physicochemical properties to evaluate a solvent effect on the reaction.